Impact of substrate elasticity on human hematopoietic stem and progenitor cell adhesion and motility - Lee-Thedieck, Cornelia; Fiammengo, Roberto; Spatz, Joachim P. (Journal of cell science, 2012)
In the bone marrow, hematopoietic stem cells (HSCs) reside in endosteal and vascular niches. The interactions with the niches are essential for the maintenance of HSC number and properties. Although the molecular nature of these interactions is well understood, little is known about the role of physical parameters such as matrix elasticity. Osteoblasts, the major cellular component of the endosteal HSC niche, flatten during HSC mobilization. We show that this process is accompanied by osteoblast stiffening, demonstrating that not only biochemical signals but also mechanical properties of the niche are modulated. HSCs react to stiffer substrates with increased cell adhesion and migration, which could facilitate the exit of HSCs from the niche. These results indicate that matrix elasticity is an important factor in regulating the retention of HSCs in the endosteal niche and should be considered in attempts to propagate HSCs in vitro for clinical applications.